Speech and audio signal processing : processing and perception of speech and music - Gold, Bernard; Morgan, Nelson (New York : Wiley, 2000)
"Speech and Audio Signal Processing provides the most current and comprehensive coverage of speech and audio signal processing available today. These topics include everything from basic foundation material on digital signal processing, pattern recognition acoustics, and hearing to material of historical significance not found anywhere else. The text also contains a range of applications of the technology, with strong focus on speech recognition and coding."--BOOK JACKET.
Ch. 22. Feature Extraction for ASR. Ch. 23. Linguistic Categories for Speech Recognition. Ch. 24. Deterministic Sequence Recognition for ASR. Ch. 25. Statistical Sequence Recognition. Ch. 26. Statistical Model Training. Ch. 27. Discriminant Acoustic Probability Estimation. Ch. 28. Speech Recognition and Understanding -- Pt. VII. Synthesis and Coding. Ch. 29. Speech Synthesis. Ch. 30. Pitch Detection. Ch. 31. Vocoders. Ch. 32. Low-Rate Vocoders. Ch. 33. Medium-Rate and High-Rate Vocoders -- Pt. VIII. Other Applications. Ch. 34. Speech Transformations. Ch. 35. Some Aspects of Computer Music Synthesis. Ch. 36. Speaker Verification.
Includes bibliographical references and index.
Keywords: Speech processing systems; Signal processing -- Digital techniques